Investigation of the Effects of Biological Activity and Steeping Time of Four Different Black Teas Commercially Valuable in Turkey - TAŞKIN, TURGUT (MARMARA UNIV, INST HEALTH SCIENCES, 2019)
Objective: The aim of this study was to compare the phenolic, tannins contents and biological activities (antioxidant, anticholinesterase) of four different black teas commercially valuable in Turkey. Subsequently, to examine the effect of the steeping time on the chemical contents (phenolic and tannins contents) and biological activities of the samples. Methods: The antioxidant activities of samples were examined by 2,2-diphenyl-1-picryl-hydrazyl (DPPH), cupric reducing antioxidant capacity (CUPRAC) and ferric reducing/antioxidant power (FRAP) methods. The amount of total phenolic and tannins contents contained in the samples was determined using the Folin-Ciocalteu reagent (FCR) method. In addition, the anticholinesterase activities of different samples were evaluated by Ellman method. Results: According to the results obtained, filtered tea bag (FT) sample obtained after 5 min steeping exhibited stronger DPPH radical scavenging activity than other samples. In addition, it was found that powder ceylon tea (PCT) samples obtained after 60 min and 10 min steeping had the highest FRAP and CUPRAC values respectively. In this study, it was also determined that the PCT samples obtained after 5 min, 10 min, 15 min, and 30 min steeping contained higher phenolic and tannins contents than the other samples. In anticholinesterase experiment, powder tea (PT) sample obtained after 5 min steeping was found to have the strongest anticholinesterase activity. Conclusion: As a result, it was determined that the amount of phenolic contents generally increased with the infusion time. It was also found that the antioxidant, anticholinesterase activities and tannins content of the tea samples did not show significant change due to the time of the infusion.
Keywords: Black teas; antioxidant; anticholinesterase; steeping time; ANTIOXIDANT ACTIVITY; GREEN; EXTRACTION; CATECHIN; LEAVES